Cell-Mediated Immunological Biomarkers and Their Diagnostic Application in Livestock and Wildlife Infected With Mycobacterium bovis - Smith, Katrin; Kleynhans, Léanie; Warren, Robin M.; Goosen, Wynand J.; Miller, Michele A. (Frontiers in Immunology, 2021)
Mycobacterium bovis has the largest host range of the Mycobacterium tuberculosis complex and infects domestic animal species, wildlife, and humans. The presence of global wildlife maintenance hosts complicates bovine tuberculosis (bTB) control efforts and further threatens livestock and wildlife-related industries. Thus, it is imperative that early and accurate detection of M. bovis in all affected animal species is achieved. Further, an improved understanding of the complex species-specific host immune responses to M. bovis could enable the development of diagnostic tests that not only identify infected animals but distinguish between infection and active disease. The primary bTB screening standard worldwide remains the tuberculin skin test (TST) that presents several test performance and logistical limitations. Hence additional tests are used, most commonly an interferon-gamma (IFN-γ) release assay (IGRA) that, similar to the TST, measures a cell-mediated immune (CMI) response to M. bovis. There are various cytokines and chemokines, in addition to IFN-γ, involved in the CMI component of host adaptive immunity. Due to the dominance of CMI-based responses to mycobacterial infection, cytokine and chemokine biomarkers have become a focus for diagnostic tests in livestock and wildlife. Therefore, this review describes the current understanding of host immune responses to M. bovis as it pertains to the development of diagnostic tools using CMI-based biomarkers in both gene expression and protein release assays, and their limitations. Although the study of CMI biomarkers has advanced fundamental understanding of the complex host-M. bovis interplay and bTB progression, resulting in development of several promising diagnostic assays, most of this research remains limited to cattle. Considering differences in host susceptibility, transmission and immune responses, and the wide variety of M. bovis-affected animal species, knowledge gaps continue to pose some of the biggest challenges to the improvement of M. bovis and bTB diagnosis.